2020
DOI: 10.18805/ijar.b-1268
|View full text |Cite
|
Sign up to set email alerts
|

The Promotion of Peony Seed Proteolysis Product to the Immune Efficacy Induced by ptfA Gene DNA Vaccine of Avian Pasteurella multocida

Abstract: Background: Avian Pasteurella multocida is one of the pathogens that affect the health of poultry. The protective efficacy of traditional attenuated vaccine is not ideal. In previous study, we prepared ptfA gene DNA vaccine of avian P. multocida. However, the protective effect of ptfA gene DNA vaccine was inferior to the attenuated vaccine. Therefore, it is necessary to improve the immune efficacy of avian P. multocida DNA vaccine, such as screening for novel adjuvant. Methods: In this study, the peony seed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Current vaccines are required to administer parentally, booster dose and are less efficacious (Proceeding of FAO/ APHCA workshop on HS 1991). Earlier studies showed that vaccination of buffaloes and poultry with killed bacteria generally results in serotype-specific immunity (Carpenter et al, 1991;Qiang et al, 2020;Shukla et al, 2021) whereas, heterologous protection is conferred only with the attenuated strain (Elena Garrido et al, 2008;W affa et al, 2014;Myint. 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Current vaccines are required to administer parentally, booster dose and are less efficacious (Proceeding of FAO/ APHCA workshop on HS 1991). Earlier studies showed that vaccination of buffaloes and poultry with killed bacteria generally results in serotype-specific immunity (Carpenter et al, 1991;Qiang et al, 2020;Shukla et al, 2021) whereas, heterologous protection is conferred only with the attenuated strain (Elena Garrido et al, 2008;W affa et al, 2014;Myint. 2000).…”
Section: Resultsmentioning
confidence: 99%